How tariffs are conceptually reflected in key economic statistics - Statistics Canada (Economic and Social Reports)
The effects of tariffs on Canadian exports or on imports into Canada will, over time (as they affect economic activities), be reflected in various statistical estimates published by Statistic Canada. While some programs measure tariffs directly - others do not, due to their underlying concepts. However, the impact of tariffs is embedded in data collected across multiple statistical programs which is used to calculate estimates like the Consumer Price Index, various producer price indexes, retail and manufacturing sales and key macroeconomic indicators, including the balance of payments, gross domestic product, supply and use tables, and government finances. This note outlines how these effects are captured across various statistical programs.